(cosec 0 - cot 0)^2 = 1 + cos0/1 - cos0
Answers
Answered by
58
To Prove
→ (cosec∅ - cot∅)² = (1 - cos∅)/(1 + cos∅)
Solution
By replacing values of cosec∅ and cot∅.
L.H.S → (1/sin∅ - cos∅/sin∅)²
→ [(1 - cos∅)/sin∅]²
→ (1 - cos∅)²/sin²∅
Since sin²∅ = 1 - cos²∅
→ (1 - cos∅)²/(1 - cos²∅)
By a² - b² identity we get (1 - cos∅)(1 + cos∅)
→ (1 - cos∅)(1 - cos∅)/(1 - cos∅)(1 + cos∅)
→ (1 - cos∅)/(1 + cos∅) = R.H.S
Q.E.D
Answered by
13
Step-by-step explanation:
i hope this will help you
Attachments:
![](https://hi-static.z-dn.net/files/d5f/134522235f4bbfa4e2941f707284eafe.jpg)
Similar questions